Semiautomated Software to Improve Stability and Reduce Operator‐Induced Variation in Vascular Ultrasound Speckle Tracking. (16th February 2022) - Rajaram, Nirmala; Thelen, Brian J.; Hamilton, James D.; Zheng, Yihao; Morgan, Timothy; Funes‐Lora, Miguel Angel; Yessayan, Lenar; Shih, Albert J.; Henke, Peter; Osborne, Nicholas; Bishop, Brandie; Krishnamurthy, Venkataramu N.; et al.
Abstract : Objectives: Ultrasound is useful in predicting arteriovenous fistula (AVF) maturation, which is essential for hemodialysis in end‐stage renal disease patients. We developed ultrasound software that measures circumferential vessel wall strain (distensibility) using conventional ultrasound Digital Imaging and Communications in Medicine (DICOM) data. We evaluated user‐induced variability in measurement of arterial wall distensibility and upon finding considerable variation we developed and tested 2 methods for semiautomated measurement. Methods: Ultrasound scanning of arteries of 10 subjects scheduled for AVF surgery were performed. The top and bottom of the vessel wall were tracked using the Kanade‐Lucas‐Tomasi (KLT) feature‐tracking algorithm over the stack of images in the DICOM cine loops. The wall distensibility was calculated from the change of vessel diameter over time. Two semiautomated methods were used for comparison. Results: The location of points selected by users for the cine loops varied significantly, with a maximum spread of up to 120 pixels (7.8 mm) for the top and up to 140 pixels (9.1 mm) for the bottom of the vessel wall. This variation in users' point selection contributed to the variation in distensibility measurements (ranging from 5.63 to 41.04%). Both semiautomated methods substantially reduced variation and were highly correlated with the median distensibility values obtained by the 10 users. Conclusions: Minimizing user‐induced variation by standardizing point selection will increase reproducibility and reliability of distensibility measurements. Our recent semiautomated software may help expand use in clinical studies to better understand the role of vascular wall compliance in predicting the maturation of fistulas.